Effect of Forest Management Types on Soil Carbon Stocks in Montane Forests: A Case Study of Eastern Mau Forest in Kenya - George K. Tarus; Stanley W. Nadir (International Journal of Forestry Research)
Mau Forest, a major forest reserve in Kenya, has experienced anthropogenic disturbances through encroachment and forest fires. This study aimed at comparing the soil carbon stocks in different forest management types as well as how seasonal climatic changes influence its dynamics. The study was undertaken in the Eastern Mau block (Sururu) which forms part of the greater Mau Forest Complex. The forest management interventions have been in place for over 15 years with disturbed (fire) natural forest experiencing fires in 2005, 2007, and 2014 while cypress plantations were established in 1994. A nested experimental design was used in data collection, where thirty-two sample plots were nested into four blocks each measuring 100 m2 delineated by forest management types (disturbed by fire, natural forest, undisturbed natural forest, plantation, and glades). In each plot, data on soil carbon stocks, soil bulk density, soil moisture, and temperature were collected for both dry and wet seasons. Data collection was carried out between November 2015 and December 2016. The results indicated that there were no significant differences in the carbon stocks among the forest management types (F4,16 = 0.61, P=0.613). However, seasonal weather changes significantly affected the amount of carbon stocks among the forest management types (F4,16 = 0.61, P>0.05). The undisturbed natural forest had the highest mean soil carbon stocks, while the plantation forest had the lowest as follows: undisturbed natural forest (135.17 ± 35.99.0 Mg·C−ha), disturbed natural forest by fire (134.52 ± 38.11 Mg·C−ha), glades (122.4 ± 64.9 Mg·C−ha), and plantation forest (116.51 ± 39.77 Mg·C−ha). Furthermore, the undisturbed natural forest management had the highest bulk density (0.66 g/cm3), while the disturbed (fire) natural forest had the lowest (0.59 g/cm3). These values were low compared to most normal mineral soils which have a bulk density of between 1.0 g/cm3 and 1.5 g/cm3. There was a significant (P>0.01) relationship between seasonal weather (temperature) changes and soil carbon stocks under different forest management types with the relationship being stronger in soils under glades (r2 = 0.62) and weak in the undisturbed natural forest (r2 = 0.26). In conclusion, forest disturbances have an impact on soil carbon stocks, and for effective management of forest towards climate stabilization, then disturbance should be minimized if not avoided.